2019
DOI: 10.3389/fcell.2019.00248
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Liver Due to Increased de novo Lipogenesis: Alterations in the Hepatic Peroxisomal Proteome

Abstract: In non-alcoholic fatty liver disease (NAFLD) caused by ectopic lipid accumulation, lipotoxicity is a crucial molecular risk factor. Mechanisms to eliminate lipid overflow can prevent the liver from functional complications. This may involve increased secretion of lipids or metabolic adaptation to ß-oxidation in lipid-degrading organelles such as mitochondria and peroxisomes. In addition to dietary factors, increased plasma fatty acid levels may be due to increased triglyceride synthesis, lipolysis, as well as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 56 publications
2
35
0
1
Order By: Relevance
“… 39 Indeed, inhibiting mitochondrial pyruvate import 40 , 41 or mitochondrial citrate export 42 has been shown to reduce DNL and/or revert NAFLD/NASH. In addition, several investigators have shown that increased DNL is a hallmark of NAFLD in both mouse 43 , 44 and human studies. 45 , 46 , 47 Taken together, we believe L-PK–mediated regulation of pyruvate oxidation and DNL is causal in developing steatosis and eventually fibrosis, and limiting this could have a therapeutic potential against NAFLD.…”
Section: Discussionmentioning
confidence: 99%
“… 39 Indeed, inhibiting mitochondrial pyruvate import 40 , 41 or mitochondrial citrate export 42 has been shown to reduce DNL and/or revert NAFLD/NASH. In addition, several investigators have shown that increased DNL is a hallmark of NAFLD in both mouse 43 , 44 and human studies. 45 , 46 , 47 Taken together, we believe L-PK–mediated regulation of pyruvate oxidation and DNL is causal in developing steatosis and eventually fibrosis, and limiting this could have a therapeutic potential against NAFLD.…”
Section: Discussionmentioning
confidence: 99%
“…Several peroxisomal oxidases generate hydrogen peroxide during the oxidative activities in the peroxisomes [42][43][44]. NADPH oxidases, the main source of ROS in several liver diseases, generate superoxide anions in the mitochondria by transferring a single electron from NADPH to molecular oxygen [45][46][47].…”
Section: Oxidative Stressmentioning
confidence: 99%
“…Recently, due to the advantages of high-throughput methods, such as genomics, proteomics and lipidomics, systematic analyses of genes, proteins, and metabolites have been utilized to provide more comprehensive information to understand the physiological and pathological processes of various diseases. Several studies have applied proteomic and lipidomic analyses to comprehensively dissect the homeostasis of proteins and lipids in NAFLD [ 9 , 10 ]. However, no studies have focused on global changes in proteins and lipids in NAFLD treated with Kaili Sour Soup.…”
Section: Discussionmentioning
confidence: 99%